Applied economics and public policy : edited by Iain Begg and G. S. B. Henry - Economics--Methodology--Congresses; Henry, G. S. B.. (United Kingdom : Cambridge University, 1998)
Papers presented at a conference on Dec 15-16, 1995 to mark the 50th Anniversary of the the founding of the Department of Applied Economics, Cambridge University
Keywords: Economic policy -- Methodology -- Congresses; Europe -- Economic conditions -- Statistical methods-Congresses.